Community Service-Based Financial Education for Sustainable Economic Development in the United States - M. Neeharika (CV Edujavare Publishing, 2024)
The rapid development of global economic systems and digital financial technology has increased the importance of financial literacy in contemporary society. Financial education is considered an essential strategy for improving economic awareness, responsible financial behavior, and sustainable community development. This community service program aims to strengthen financial literacy through community-based financial education for sustainable economic development in the United States. The program employed a qualitative participatory approach involving students, workers, families, and community members through workshops, mentoring activities, financial simulations, and collaborative learning sessions. Participants were introduced to financial management concepts, budgeting strategies, savings planning, digital financial systems, and responsible economic decision-making practices. The results demonstrated that participants experienced significant improvement in financial awareness, budgeting competence, digital financial adaptability, and confidence in managing personal finances. In addition, collaborative educational activities encouraged active participation, problem-solving abilities, and understanding of ethical financial behavior among participants. Despite challenges related to differences in educational backgrounds, technological familiarity, and access to financial resources, continuous mentoring and participatory learning strategies contributed positively to the implementation process. Overall, community service-based financial education provided valuable opportunities for improving financial literacy, strengthening economic resilience, and supporting sustainable community development. The experiences implemented in the United States can also serve as important references for developing sustainable financial literacy and community empowerment programs in various educational and social contexts worldwide.